2001
DOI: 10.1074/jbc.m101939200
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Acute Regulatory Protein Binds Cholesterol and Modulates Mitochondrial Membrane Sterol Domain Dynamics

Abstract: The steroidogenic acute regulatory protein (StAR) mediates the rate-limiting step of steroidogenesis, delivery of cholesterol to the inner mitochondrial membrane. However, the mechanism whereby cholesterol translocation is accomplished has not been resolved. Recombinant StAR proteins lacking the first N-terminal 62 amino acids comprising the mitochondrial-targeting sequence were used to determine if StAR binds cholesterol and alters mitochondrial membrane cholesterol domains to enhance sterol transfer. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 55 publications
8
108
3
Order By: Relevance
“…Initial calculations indicated that the StarD4 tunnel volume is 1,424 Ϯ 294 Å 3 (a similar value of 1,820 Ϯ 481 Å 3 was observed with MLN64). These results compare favorably with the previously reported estimate of 1,900 Å 3 for MLN64 (8), which is compatible with the binding of two molecules of cholesterol (28). Visual inspection of the two tunnels, however, suggests that only one cholesterol molecule can be accommodated by either protein.…”
Section: Resultssupporting
confidence: 81%
“…Initial calculations indicated that the StarD4 tunnel volume is 1,424 Ϯ 294 Å 3 (a similar value of 1,820 Ϯ 481 Å 3 was observed with MLN64). These results compare favorably with the previously reported estimate of 1,900 Å 3 for MLN64 (8), which is compatible with the binding of two molecules of cholesterol (28). Visual inspection of the two tunnels, however, suggests that only one cholesterol molecule can be accommodated by either protein.…”
Section: Resultssupporting
confidence: 81%
“…However, SCP-2 overexpression still reduced the early exchange of sterol as seen by the 6-fold reduction in initial rate by shifting most of the sterol into the nonexchangeable pool (173). In part, this might explain the large pool of non-exchangeable sterol observed in exchange assays using mitochondrial membrane vesicles isolated from steroidogenic MA-10 Leydig cells (143).…”
Section: Physiological Significance Of In Vitro Studies With Dhe and mentioning
confidence: 98%
“…DHE has been used to probe the structural (polarization, limiting anisotropy, order), dynamic (lifetime, rotational rate), and kinetic (exchange) environment of cholesterol in plasma membranes (6,7,54,55,135,(138)(139)(140)(141), microsomes (6,7), mitochondria (6,7,142,143), and lysosomes (8,129). DHE has revealed several important structural and dynamic aspects of the cholesterol microenvironment in biological membranes.…”
Section: Dhe Architecture In Purified Biological Membranesmentioning
confidence: 99%
“…StAR is synthesized as a short-lived cytoplasmic 37-kDa protein with a mitochondrial leader peptide that is cleaved upon mitochondrial import to yield the long-lived intramitochondrial 30-kDa form [58]. It is now wellestablished that StAR functions as a sterol transfer protein [70], binds cholesterol [71,72], mediates the acute steroidogenic response by moving cholesterol from the outer to the inner mitochondrial membrane [73], acts on the outer mitochondrial membrane [73][74][75], and requires the structural change previously described as a pH-dependent molten globule [76]. StAR is also a prototype of a family of proteins that contain START (StAR-related lipid transfer) domains (StarD proteins) [77], of which StarD3/MLN64, StarD4, StarD5 and StarD6 exhibit steroidogenic potential [78,79].…”
Section: Hormonal Regulation Of Steroidogenesismentioning
confidence: 99%